Review—Recent Developments in the Applications of 2D Transition Metal Dichalcogenides as Electrocatalysts in the Generation of Hydrogen for Renewable Energy Conversion. Issue 6 (1st June 2022) - Sukanya, Ramaraj; da Silva Alves, Daniele C.; Breslin, Carmel B.
Abstract : There has never been a more pressing need to develop sustainable energy systems as dramatic climate changes emerge across the World. Some of these effects can be alleviated by the development of efficient devices that are capable of producing hydrogen gas in an environmentally acceptable manner, which in turn can be employed as a clean fuel. In this context, the splitting of water is especially attractive. However, this technology requires the design of new cost-effective electrocatalytic materials. In this review, the progress made in the development of transition metal dichalcogenides (TMDs) and their composites as electrocatalysts for both acidic and alkaline electrolysis cells and as photocatalysts for the formation of hydrogen is described and discussed. Following a short introduction to the mechanisms of the electrochemical hydrogen and oxygen evolution reactions and the photoelectrochemical generation of hydrogen, an introduction to TMDs, their relevant general properties and the methods used in their synthesis are described. Then, the performance of various TMD-based materials in the electrochemical splitting of water is discussed, with a final brief overview of the application of TMDs in photoelectrochemical devices. Although challenges clearly remain, TMD-based materials are emerging as promising electrocatalysts and photoelectrocatalysts for the production of hydrogen.